Questions on Linguistic Disadvantage in Writing Articles in English among Algerian University Lecturers - Abdelhadi, Amina; Founes, Oussama (Technium Social Sciences Journal, 2022)
The study at hand aims to investigate Algerian researchers’ perceptions of the importance of writing research articles for publication in international English medium journals, along with the incentives and disincentive influencing this process, and the challenges they encounter. To reach these aims, a survey is conducted with twenty six Algerian lecturers from three different fields of study using an online questionnaire created in Google Forms. The vast majority of the participants rate writing research in English as of great importance and they opt for different incentives influencing their decision to publish in international English medium journals, but they perceive themselves to be disadvantaged by their non-native status as the degree of their perceived difficulty of writing scientific articles in English is very high. This study highlights the correlation between the mastery of English as a principal prerequisite in the respondents’ fields of study and the use of English as an indispensable key to communicate their research results to the global scientific community. It then ends up with some strategies to be taken by higher education institutes to address this issue from different standpoints.